Analysis of Violent Incidents at Five Regional and Remote Australian Emergency Departments: A Retrospective Descriptive Study - Brodie Thomas; Alycia Jacob; Damhnat McCann; Penny Buykx; Rebecca Schultz; Leigh Kinsman; Peter O'Meara; Kristina Edvardsson; Evelien Spelten (SAGE Publishing, 2024)
Introduction Workplace violence is endemic, destructive, and escalating in frequency and severity in healthcare. There is a paucity of research on workplace violence in regional and remote hospital emergency departments (EDs). Objective The aim of this study was to identify the perpetrator and situational characteristics associated with violent incidents in the ED across five regional and remote Australian sites. Method This study audited hospital summary data, incident reports, and medical records for a 12-month period in 2018 to examine the perpetrator and situational characteristics of workplace violence incidents in five regional and remote Australian EDs. Results Violent incidents were evenly spread throughout the week and across shifts. Most incidents were triaged as urgent, occurred within the first 4 hr, and had multidisciplinary involvement. Almost one in every six incidents resulted in an injury. Perpetrators of violence were predominantly young and middle-aged males and almost always patients, with most presenting with mental and behavioral disorders, or psychoactive substance use. Conclusions Understanding the characteristics of perpetrators of violence can help in seeking to tailor interventions to reduce further violent behaviors. These findings carry implications for optimizing patient care, staff safety and resource management.